2019
DOI: 10.1088/1757-899x/593/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of Chitosan Adhesive from Shell Shrimp Litopenaeus vannamei and Their Application For Producing Particleboard

Abstract: The shrimp shell that rich compounds of chitin can be converted to produce polysaccharides called chitosan. The chitosan can be utilized as bioadhesive for substitute chemical based adhesive for producing particleboard. The purpose of this study was to evaluate the effect of different concentration acetic acid (CH3COOH) as the solvent to made chitosan adhesive and physical and mechanical properties of the produced particleboard by using sawdust waste. Chitosan adhesive formulation will be used as an adhesive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…There is evidence that chitosan can be used as coagulant in wastewater treatment plants [66]. Chitosan is electrostatically attracted to negatively charged surfaces, which is possible because the deacylation of chitin leaves a free -NH3 + group [67], [68]. The polarity of chitosan means that this adhesive also binds water well, so the properties of the wood deteriorate in the presence of water.…”
Section: Sources Of Bio-based Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that chitosan can be used as coagulant in wastewater treatment plants [66]. Chitosan is electrostatically attracted to negatively charged surfaces, which is possible because the deacylation of chitin leaves a free -NH3 + group [67], [68]. The polarity of chitosan means that this adhesive also binds water well, so the properties of the wood deteriorate in the presence of water.…”
Section: Sources Of Bio-based Adhesivesmentioning
confidence: 99%
“…The positive aspect of chitosan is its production potential from the production residues of other products, so it can become a by-product, such as in production of shelled shrimp [67].…”
Section: Sources Of Bio-based Adhesivesmentioning
confidence: 99%
“…For instance, Ningsi et al extracted chitin from shrimp shells and converted it to chitosan, applying it as raw material for particleboard adhesives. The mechanical properties of these panels satisfied the requirements for the P2 panel type [12]. Starch extracted from palm oil was crosslinked with epichlorohydrin and applied to gluing rubberwood particleboards.…”
Section: Introductionmentioning
confidence: 92%
“…Meanwhile, Ji et al [40,41] has been used ASC as an adhesive that combined with glutaraldehyde for medium density berboard (MDF) and with lignin made of sawdust. The study conducted by Ningsi et al [42] showed that particleboard bonded with ASC as an adhesive still has limited at dimensional stability, screw holding power and internal bonding properties.…”
Section: Introductionmentioning
confidence: 99%